THE USE OF INNOVATIVE TECHNOLOGIES IN PHYSICS LESSONS - Madaminova Fazilat Ganisherovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Today's modern world encourages us to look at every detail of education in a modern way. In addition to teaching each subject in a way that integrates modern innovative technologies, it is one of the most pressing issues today. This article describes in detail the importance of physics in the world community and the use of innovative technologies in teaching this subject to students.